Investigation of the effects of SOA locations in the linear cavity of an O-band Brillouin SOA fiber laser - Ahmad, Harith; Norizan, Siti Fatimah; Zulkifli, Mohd Zamani; Pua, Chang Hong; Abdul Ghani, Zawajer; Harun, Sulaiman Wadi (Taylor & Francis, 2011)
An investigation into the effect of semiconductor optical amplifier (SOA) location in an O-band Brillouin SOA fiber laser (BSFL) was performed. Better output peak power flatness was generated by placing the SOA after the nonlinear medium, which is a 20 km true wave fiber (TWF) than placing it before the TWF. A maximum power of six flat output peaks with average power of - 22.0 dBm for a BP (Brillouin pump) wavelength of 1320 nm was obtained, generated from a BSFL with a SOA located after the TWF, compared with three flat Stokes signals with the SOA before the TWF at a BP wavelength of 1310 nm. The flat peak power output for the O-band Brillouin fiber laser is important, especially in producing a good O-band source.